An Exploratory Study to Assess the Knowledge Regarding Enteral Feeding among Staff Nurses in Christian Medical College & Hospital, Ludhiana, Punjab (International Journal of Nursing Education, 2019)
Nasogastric tube feeding is the most frequently used method of enteral feeding particularly if feeding is to be used for short period. The nurse’s knowledge in tube feeding and subsequent care of nasogastric tube are important in clinical area to ensure patient safety. Present study was conducted to assess the knowledge regarding enteral feeding among staff nurses in Christian Medical College & Hospital, Ludhiana, Punjab. Objectives of the study were to assess the knowledge regarding enteral feeding among Staff Nurses, to ascertain the relationship of knowledge regarding enteral feeding among staff nurses with selected variables such as age, gender, marital status, professional qualification, work experience, working area, in- service education and to prepare the pamphlet to enhance the knowledge regarding enteral feeding among staff nurses. Quantitative research approach and non-experimental exploratory design were used in the study. Subjects were chosen by purposive sampling technique and the sample size was 100 staff nurses. Data was collected by structured multiple choice questionnaire and analyzed by using descriptive and inferential statistics. Bar diagram was used to depict the findings. Results of the study shows majority (80%) of staff nurses had good knowledge, 12% staff nurses had excellent knowledge and only 8% staff nurses had average knowledge regarding enteral feeding. Among demographic characteristics working area and marital status had significant impact on the knowledge of staff nurses regarding enteral feeding.
Keywords: Nurses, Knowledge, Enteral feed.